Moving the Cellular Peptidome by Transporters - Abele, Rupert; Tampé, Robert (Frontiers in Cell and Developmental Biology, 2018)
Living matter is defined by metastability, implying a tightly balanced synthesis and turnover of cellular components. The first step of eukaryotic protein degradation via the ubiquitin-proteasome system (UPS) leads to peptides, which are subsequently degraded to single amino acids by an armada of proteases. A small fraction of peptides, however, escapes further cytosolic destruction and is transported by ATP-binding cassette (ABC) transporters into the endoplasmic reticulum (ER) and lysosomes. The ER-resident heterodimeric transporter associated with antigen processing (TAP) is a crucial component in adaptive immunity for the transport and loading of peptides onto major histocompatibility complex class I (MHC I) molecules. Although the function of the lysosomal resident homodimeric TAPL-like (TAPL) remains, until today, only loosely defined, an involvement in immune defense is anticipated since it is highly expressed in dendritic cells and macrophages. Here, we compare the gene organization and the function of single domains of both peptide transporters. We highlight the structural organization, the modes of substrate binding and translocation as well as physiological functions of both organellar transporters.